Use of tetramethylbenzidine for the spectrophotometric sequential injection determination of free chlorine in waters - Mesquita, Raquel B. R. (2010)
A sequential injection (SI) method was developed for the spectrophotometric determination of chlorine based on the reaction between tetramethylbenzidine (TMB) and free chlorine. The advantages resulting from the use of TMB are considerable: TMB is highly selective for chlorine, it enables a fairly low quantification limit and represents a less toxic alternative to reagents such as tolidine. The use of this reaction in SI adds other advantages as it enhances the degree of automation, minimisation of reagent consumption (6.8 g TMB/assay) and low effluent production (2.5 mL/determination). The developed method allowed a quantification limit of 90 g/L with a working range of 0.09–1.30 mg OCl−/L and a determination rate of 60 det./h. Based on these features, the system was applied to tap-water and surface water samples with no previous treatment required. The results obtained with the developed system were compared to the reference method, diethyl-p-phenylelediamine (DPD) colorimetric method, and proved not to be statistically different.